Acute electrophysiologic effects of the polyphenols resveratrol and piceatannol in rabbit atria. (10th December 2018) - Frommeyer, Gerrit; Wolfes, Julian; Ellermann, Christian; Kochhäuser, Simon; Dechering, Dirk G.; Eckardt, Lars
Summary: The natural polyphenol resveratrol and its analogue piceatannol have various beneficial effects including antiarrhythmic properties. The aim of the present study was to examine potential electrophysiologic effects in an experimental whole‐heart model of atrial fibrillation (AF). Simultaneous infusion of resveratrol (50 μmol/L) or piceatannol (10 μmol/L) in rabbit hearts resulted in an increase in atrial refractory period. Both agents induced a significant slowing of atrial conduction and of intrinsic heart rate. In both groups, a trend toward a reduction in AF and a regularization of AF was observed.